Evaluasi Aktivitas Antioksidan dan Penangkapan Radikal Bebas pada Varietas Cabai (Capsicum annuum L.): Evaluation of Antioxidant and Free Radical Scavenging Activity in Chilli Cultivars (Capsicum Annum L.) - Dr.V.Krithika; Dr.S. Radhai Sri; Dr.Shanthi Dhandapani; Poovizhi T; Dr.B. Premagowri; Kamar Afshan (Amerta Nutrition, 2026)
Background: Hot peppers are an excellent source of antioxidant substances containing vitamins, phenolic compounds, capsaicinoids, and carotenoids. The concentrations of these bioactive chemicals are affected by cultivar, maturity, growing conditions, and post-harvest handling. Antioxidants are essential for neutralizing free radicals associated with oxidative stress. Objectives: To analyse the antioxidant and free radical scavenging capabilities of chilli cultivars. Methods: The research design employed in this study was experimental, in which ethanolic and methanolic extracts from different chilli cultivars (Byadagi, Sattur S4, Sangali Sannam, and Tomato Chilli) were evaluated for their Antioxidant  (AO) and Free Radical Scavenging (RS) activities. The variables measured include the scavenging activities against superoxide and hydroxyl radicals, as well as enzymatic and non-enzymatic antioxidant activities. Radical Scavenging activities were  assessed using appropriate assays in a concentration-dependent manner, while antioxidant activities were quantified through standard methods. Data were analysed using Duncan's Multiple Range Test followed by one-way ANOVA to determine significant differences between cultivars and extract types, providing insight into their potential as natural antioxidants. Results: Among the tested chilli varieties, the Byadagi variety exhibited the highest enzymic (SOD=400±0.04), (GST=1.613±0.10), (GPx=3.011±0.21) and non-enzymic (Ascorbic acid=1.613±0.10) antioxidant activity. The Radical Scavenging activity of the methanolic extracts found to increase with concentration, demonstrating a strong correlation between concentration and antioxidant potential across all varieties. Conclusions: This study elucidated the bioactive properties of chilli extracts, highlighting them as potent sources of natural antioxidants. The findings suggest that the Byadagi variety intended at reducing oxidative stress.